Sex disparities in clinical characteristics and prognosis of immunoglobulin G4-related disease: a prospective study of 403 patients - Wang, Liwen; Zhang, Panpan; Zhang, Xia; Lin, Wei; Tang, Hanqi; Li, Jieqiong; Wang, Mu; Liu, Xiaowei; Fei, Yunyun; Chen, Hua; Peng, Linyi; Zhang, Li; et al. (Rheumatology (Oxford, England), 2019)
Abstract Objectives To study the impact of sex on the clinical presentation of IgG4-related disease (IgG4-RD). Methods We prospectively enrolled 403 newly diagnosed IgG4-RD patients. We compared the demographic features, clinical manifestations, organ involvement, laboratory tests and treatment outcomes between female and male patients. The organs involved were divided into superficial organs (salivary glands, lacrimal glands, orbit, sinus and skin) and internal organs (all the other organs). The patients treated with glucocorticoids with or without additional immunosuppressants were included in the assessment of treatment outcomes, and potential confounding factors were corrected by propensity score matching or multivariate Cox regression analysis. Results Female patients showed younger age at both symptom onset and diagnosis, and a longer interval between symptom onset and diagnosis. Allergy history, Mikulicz's disease and thyroiditis were more common in female patients, while autoimmune pancreatitis, sclerosing cholangitis and retroperitoneal fibrosis were more common in male patients. In accordance, female patients more frequently presented with superficial organ involvement, while male patients more frequently had internal organ involvement, and the discrepancy was more prominent in the patients with older age. Male sex was associated with higher peripheral eosinophils, CRP and IgG4 levels at baseline. In response to glucocorticoid-based therapies, male sex was associated with a higher IgG4-RD responder index during follow-up as well as a greater risk of relapse (hazard ratio 3.14, P = 0.003). Conclusion Our study revealed the sex disparities in clinical characteristics of IgG4-RD, and indicated that male sex was independently associated with worse prognosis in response to glucocorticoid-based therapies.